2020
DOI: 10.3390/su12229668
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Skills Assessment in Initial Teacher Training in Physical Education

Abstract: This paper assessed the impact of two teacher training degrees in Physical Education, one focusing on primary school teaching and the other one concerning secondary school teaching. Data from students of both degrees were statistically compared and contrasted taking into account four training scopes from the Questionnaire of Perception of Teaching Skills in Physical Education. A three-stage analysis was carried out: (i) a descriptive stage, (ii) an invariance analysis, and (iii) a comparison of latent means ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
2
8
0
3
Order By: Relevance
“…Evidence from the findings reveals the development of different pedagogical competencies by preservice teachers during their university education. This is consistent in literature, as exemplified in a study that explored the teaching skills assessment in teacher training in Physical Education (Aparicio-Herguedas et al, 2020). The study reported the development of skills in managing the teaching and learning process in Physical Education (Aparicio-Herguedas et al, 2020).…”
Section: Pedagogical Skills and Self-confidencesupporting
confidence: 79%
See 1 more Smart Citation
“…Evidence from the findings reveals the development of different pedagogical competencies by preservice teachers during their university education. This is consistent in literature, as exemplified in a study that explored the teaching skills assessment in teacher training in Physical Education (Aparicio-Herguedas et al, 2020). The study reported the development of skills in managing the teaching and learning process in Physical Education (Aparicio-Herguedas et al, 2020).…”
Section: Pedagogical Skills and Self-confidencesupporting
confidence: 79%
“…This is consistent in literature, as exemplified in a study that explored the teaching skills assessment in teacher training in Physical Education (Aparicio-Herguedas et al, 2020). The study reported the development of skills in managing the teaching and learning process in Physical Education (Aparicio-Herguedas et al, 2020). The study also highlighted preparation in the aspect of lesson planning, choice and use of relevant teaching aids as benefits gained from initial theoretical lessons.…”
Section: Pedagogical Skills and Self-confidencesupporting
confidence: 74%
“…Regarding the first question, 76.5% denied being prepared to deal with the diversity of their students’ educational needs. In this way, one study performed with PE teachers [ 53 ] showed that initial preparation was insufficient to develop the competencies related to inclusive education. Concerning the responses to the second question, 71.5% claimed to have been prepared through ongoing preparation to face diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Competency-based evaluation provides a comprehensive evaluation to inclusive students, which is obtained from the results of (1) Integrated learning scores; (2) consideration of student needs; (3) assessment recording system, (4) competency check that has been exceeded (Aparicio-Herguedas et al, 2020).…”
Section: Figure 2 Ois Components Frameworkmentioning
confidence: 99%